2010
DOI: 10.1186/1471-2156-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Compilation of a panel of informative single nucleotide polymorphisms for bovine identification in the Northern Irish cattle population

Abstract: Background Animal identification is pivotal in governmental agricultural policy, enabling the management of subsidy payments, movement of livestock, test scheduling and control of disease. Advances in bovine genomics have made it possible to utilise inherent genetic variability to uniquely identify individual animals by DNA profiling, much as has been achieved with humans over the past 20 years. A DNA profiling test based on bi-allelic single nucleotide polymorphism (SNP) markers would offer consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
2
15
1
4
Order By: Relevance
“…These systems usually include a first step in which SNPs are preselected and a second step in which different assignment methods are applied (Bertolini et al, 2015). For example, Allen et al (2010) in a study on Irish cattle, reported a set of 43 SNPs for breed identification on the basis of allele frequency. Heaton et al (2014) identified 163 SNPs for use in parentage testing and traceability in sheep, using the minor allele frequency (>0.3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems usually include a first step in which SNPs are preselected and a second step in which different assignment methods are applied (Bertolini et al, 2015). For example, Allen et al (2010) in a study on Irish cattle, reported a set of 43 SNPs for breed identification on the basis of allele frequency. Heaton et al (2014) identified 163 SNPs for use in parentage testing and traceability in sheep, using the minor allele frequency (>0.3).…”
Section: Discussionmentioning
confidence: 99%
“…The main result was the selection of 48 SNPs from a whole set of 48 068 and these contained sufficient genetic information to produce sufficient power for individuals' breed assignment, using a relatively low number of individuals for breed and closely related breeds. The majority of the SNPs are in non-coding/intergenic regions of the sheep genome (Supplementary Material Table S1) which is ideal for identification and assignment purpose since these regions/ SNPs should be less influenced by natural or artificial selection (Allen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies designed strategies to sample the entire genetic diversity in beef cattle or purebred populations and simulated populations of purebred gene frequencies have been used to estimate the resolution and sensitivity of these methods in identifying individuals and in parental analysis (Table S7) (Heaton et al , 2002; Werner et al , 2004; López Herráez et al , 2005; Van Eenennaam et al , 2007; Baruch and Weller, 2008; Karniol et al , 2009; Allen et al , 2010; Hara et al , 2010a,b). …”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Fernández et al (2013) showed that even in a Brazilian inbred Angus herd that only 24 SNP were needed to obtain the equivalent matching probability (MP) for parental verification as 18 microsatellites. Similarly, 43 SNP provided 2–4 orders of magnitude grater MP than 11 MS in 6 Northern Ireland cattle breeds (Aberdeen Angus, Belgian Blue, Charolais, Holstein, Limousin, and Simmental) (Allen et al, 2010). …”
Section: Introductionmentioning
confidence: 99%